2019
DOI: 10.1097/tp.0000000000002632
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of a Weight-based Dosing Regimen of Valganciclovir for Cytomegalovirus Prophylaxis in Pediatric Solid-organ Transplant Recipients

Abstract: Background. Valganciclovir has been widely used for cytomegalovirus (CMV) prophylaxis in solid-organ transplant recipients. However, the optimal dosing protocol and target exposure in children are still unclear. Specific data as to the efficacy and safety of low-dose/low-exposure regimens are lacking and urgently needed. Methods. During 2010 to 2015, the clinical efficacy and safety of a weight-based regimen of valganciclovir of 17 mg/kg/day, with a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…As only 8 of these breakthrough events occurred after dose reduction for presumed valGCV-associated adverse events (VAAE), one possible conclusion from this study may be that weight-based dosing leads to an unacceptably high level of breakthrough CMV DNAemia. Breakthrough rates of CMV DNAemia in published pSOT cohort studies using weight-based valGCV dosing range from 10% to 16%, [21][22][23][24] whereas breakthrough rates in BSA-based dosing cohorts range between 0% and 6%, [25][26][27][28][29] with one study having an outlier breakthrough rate of 15%. 30 Comparative studies that evaluate the impact of both dosing strategies on virologic and clinical outcomes are needed to answer this question.…”
Section: In the Present Issue Ofmentioning
confidence: 99%
“…As only 8 of these breakthrough events occurred after dose reduction for presumed valGCV-associated adverse events (VAAE), one possible conclusion from this study may be that weight-based dosing leads to an unacceptably high level of breakthrough CMV DNAemia. Breakthrough rates of CMV DNAemia in published pSOT cohort studies using weight-based valGCV dosing range from 10% to 16%, [21][22][23][24] whereas breakthrough rates in BSA-based dosing cohorts range between 0% and 6%, [25][26][27][28][29] with one study having an outlier breakthrough rate of 15%. 30 Comparative studies that evaluate the impact of both dosing strategies on virologic and clinical outcomes are needed to answer this question.…”
Section: In the Present Issue Ofmentioning
confidence: 99%
“…The efficacy of the pre-emptive protocol has been studied in some trials. In the study by Pappo et al [ 72 ], liver-transplanted children were given oral valganciclovir 17 mg/kg/d for 3-6 mo, leading to a decrease in the incidence of CMV infection. A study by Ueno et al [ 73 ], reported that the incidence of CMV infection in patients with 1 year prophylaxis decreased by more than 80.5% compared with a regimen of less than 1 year.…”
Section: Preventionmentioning
confidence: 99%
“…Limited evidence suggests that 6 months of prophylaxis may be associated with a lower rate of late-onset disease than 3 month regimens in CYP receiving valganciclovir [7], however, the committee agreed to propose a recommendation for 'at least 3 months' of valganciclovir due to concerns about its significant side effect profile (infection, diarrhoea, leukopenia, neutropenia) [8].…”
Section: Rationalementioning
confidence: 99%